Behavioral benefits of trazodone are sustained for the long term in frontotemporal dementia. Issue 1 (January 2006) - Lebert, Florence
Objective : Previously, a placebo-controlled cross-over trial of trazodone (300  mg/day) of 12-weeks duration showed behavioral improvement in a group of 26 patients with frontotemporal dementia. The long-term efficacy and safety of trazodone in frontotemporal dementia was unknown.Materials & methods : The placebo-controlled trial has now been followed by an open-label extension study. The 26 frontotemporal dementia patients with mild cognitive decline and severe behavioral troubles who entered the study had previously completed the double-blind study with trazodone. Patients were treated with 300  mg/day. They were followed for at least 2  years, after the end of the double-blind trial. The efficacy was evaluated by the neuropsychiatric inventory score.Results : The withdrawal rate was approximately 23% during the first  year, two patients died due to unrelated causes, two patients were institutionalized and two refused the follow-up –– none as a result of adverse events. The withdrawal rate was approximately 15% during the second year due to an increase dementia with a decrease in behavioral troubles. The mean duration of follow-up by the remaining 16 frontotemporal dementia patients was 36.7  months (±±11.5). In this group, no patient had an increase of final neuropsychiatric inventory score compared with baseline. The mean difference of neuropsychiatric inventory score between baseline and final was 20.5 (±±9.5). The neuropsychiatric inventory score was significantly lower at follow-up than at baseline (p  <  0.0005). Regarding cognition, nine of the 16 had a decrease of mini mental state examination of more than three points compared with baseline score and 7/16 had no decrease or minor decrease in mini mental state examination. Hypotension was the single side effect, observed at long term follow-up in four patients.Conclusion: The follow-up trazodone study demonstrates that trazodone is well tolerated and is effective in the long-term control of behavioral difficulties associated with frontotemporal dementia.